How To Forge Market Channels Belongs To Yorself--A Case Study Of TCL Company Channel Strategic - Ting, Chen Zhao (2008)
This paper analyzes the development of marketing net in TCL and its existing problem, and tries to find out the reforming orientation of household appliances Self-running channels.